1999
DOI: 10.1093/clinchem/45.7.1051
|View full text |Cite
|
Sign up to set email alerts
|

Adulteration of Urine by “Urine Luck”

Abstract: Background: In vitro adulterants are used to invalidate assays for urine drugs of abuse. The present study examined the effect of pyridinium chlorochromate (PCC) found in the product “Urine Luck”. Methods: PCC was prepared and added to positive urine controls at concentrations of 0, 10, 50, and 100 g/L. The controls were assayed for methamphetamine, benzoylecgonine (BE), codeine and morphine, tetrahydrocannabinol (THC), and phencyclidine (PCP) with the Emit II (Syva) and Abuscreen Online (Roche)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 3 publications
1
33
0
2
Order By: Relevance
“…[13][14][15] Previous studies related to adulterated drug samples have been carried out on other immunoassay techniques including RIA, 5 cloned enzyme donor immunoassay, 16,17 enzyme immunoassay, 18 FPIA, 7 and EMIT. [19][20][21] In a separate study, eye drops, liquid bleach, and vinegar were used to adulterate urine samples at a 10% v/v concentration and analyzed using FPIA, demonstrating that these adulterants significantly interfered with the accurate detection of cannabinoids. 14 Eye drops were also observed to create false negative results for THC assays by EMIT.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Previous studies related to adulterated drug samples have been carried out on other immunoassay techniques including RIA, 5 cloned enzyme donor immunoassay, 16,17 enzyme immunoassay, 18 FPIA, 7 and EMIT. [19][20][21] In a separate study, eye drops, liquid bleach, and vinegar were used to adulterate urine samples at a 10% v/v concentration and analyzed using FPIA, demonstrating that these adulterants significantly interfered with the accurate detection of cannabinoids. 14 Eye drops were also observed to create false negative results for THC assays by EMIT.…”
mentioning
confidence: 99%
“…Active ingredients of commercial products ) in order to ascertain the level of adulteration required to significantly reduce the detectable concentrations of drugs and their metabolites by ELISA. Previous work with other immunoassay techniques have shown that adulterants will have some extent of interference with either the antibody coated well plate or the drug itself 5,13,[16][17][18][19][20][21]. …”
mentioning
confidence: 99%
“…Due to the possibility of adverse actions, service members may attempt to "beat" the drug test. Previous practices include excessive hydration hours before the specimen collection, specimen adulteration, [2][3][4][5][6][7] and specimen substitution using a prosthetic penis such as the "Whizzinator." 8 In April 2017, Diagnostic Laboratory Services (DLS) on Oahu, Hawaii, believed that the decline in methamphetamine positive specimens received and tested in DLS was due to the substitution of urine with synthetic urine (SU).…”
Section: Introductionmentioning
confidence: 99%
“…Use of surrogates, such as artificial urine, in vivo adulteration through consumption of large volumes of liquids consequently diluting urinary drug concentrations, and in vitro adulteration through addition of liquids or chemicals after urine collection. 11 Systematic studies on the prevalence of adulteration attempts are scarce and it can be assumed that such attempts are detected only in rare cases. 1,12 With recent intentions in several US states to ban artificial urine products, chemical adulteration attempts might become of higher interest.…”
mentioning
confidence: 99%